2023
DOI: 10.3390/life13030771
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of FDG Uptake of the Reticuloendothelial System with Tumor Immune Microenvironment and Prognosis in Patients with Gastric Cancer

Abstract: 2-deoxy-2-[18F]fluoro-D-glucose (FDG) uptake of the reticuloendothelial system, including the bone marrow (BM) and spleen, on positron emission tomography/computed tomography (PET/CT) has been shown to be a significant prognostic factor in diverse malignancies. However, the relationship between FDG uptake of the BM and spleen and histopathological findings, including the tumor immune microenvironment, has not been fully evaluated. This study aimed to investigate the relationship of FDG uptake in the BM and spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…In addition to primary cancer lesion imaging features, we also evaluated the relationship of FDG uptake of the BM and spleen with immunohistochemistry results. FDG uptake values in both the BM and spleen are known to be imaging biomarkers of the systemic inflammatory response to cancer cells, but both values are considered to reflect different aspects of the host’s immune response [ 18 , 24 ]. In previous studies that evaluated the relationship of FDG uptake in the BM and spleen with immunohistochemical findings in cervical and gastric cancer specimens, FDG uptake in the BM was positively associated with the degree of myeloid-derived suppressor cell and CD163 + macrophage infiltration in the tumor tissue [ 24 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to primary cancer lesion imaging features, we also evaluated the relationship of FDG uptake of the BM and spleen with immunohistochemistry results. FDG uptake values in both the BM and spleen are known to be imaging biomarkers of the systemic inflammatory response to cancer cells, but both values are considered to reflect different aspects of the host’s immune response [ 18 , 24 ]. In previous studies that evaluated the relationship of FDG uptake in the BM and spleen with immunohistochemical findings in cervical and gastric cancer specimens, FDG uptake in the BM was positively associated with the degree of myeloid-derived suppressor cell and CD163 + macrophage infiltration in the tumor tissue [ 24 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies that evaluated the relationship of FDG uptake in the BM and spleen with immunohistochemical findings in cervical and gastric cancer specimens, FDG uptake in the BM was positively associated with the degree of myeloid-derived suppressor cell and CD163 + macrophage infiltration in the tumor tissue [ 24 , 34 ]. Meanwhile, FDG uptake in the spleen was positively correlated with the degree of CD8 + T cell lymphocyte, CD20 + B cell lymphocyte, and CD68 + monocyte infiltration in the tumor tissue [ 24 , 35 ]. Furthermore, a previous study on patients with biliary tract and pancreatic cancer patients reported high serum levels of various cytokines, including IL-6, in those with high spleen FDG uptake [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a chronic systemic inflammatory condition in patients could promote the loss of VAT [ 5 , 20 ]. A chronic systemic inflammatory condition could be a potential mechanism of the relationship between a loss of VAT and recurrence risk since the systemic inflammatory condition could contribute to a favorable host environment for cancer recurrence and is associated with an increased risk of cancer recurrence in patients with gastric cancer [ 20 , 31 ]. However, further studies are needed to explicitly elucidate the underlying mechanism between a loss of VAT after surgery and gastric cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to conventional imaging modalities, 2-deoxy-2-[ 18 F]fluoro-D-glucose (FDG) positron emission tomography/computed tomography (PET/CT) has been used for accurate staging, cancer recurrence detection, and predicting clinical outcomes in patients with cholangiocarcinoma [8,11,12]. Since FDG uptake by the organ also increases in an inflammatory condition, recent studies have revealed that the systemic inflammatory response to cancer cells can be estimated by FDG PET/CT images in patients with malignant diseases [13][14][15]. Previous studies showed a significant relationship between the degree of FDG uptake in the bone marrow (BM) and spleen, which are the main primary organs of the reticuloendothelial system, with immune cell infiltration in tumor tissue and serum inflammatory markers, and also revealed the significant prognostic value of FDG uptake in the BM and spleen for predicting survival in patients with diverse malignancies [14][15][16].…”
Section: Introductionmentioning
confidence: 99%